An unusual case of giant multilobulated lipoma over left truncal region - Singh, Sandesh Bharat; Vardhan, Harsha; Chauhan, Neelam; Singh, Arun Kumar (International Surgery Journal, 2020)
Lipomas can virtually occur anywhere in the human body. They can be of varying sizes. Small lipomas are more frequently found, whereas giant lipomas are comparatively rare. These slow-growing, nearly always benign, tumors usually present as non painful, round, mobile masses with a characteristic soft, doughy feel. They are one of the most common benign tumours found in the body. Difference through histopathology and immunochemistry has to be done to rule out other conditions such as liposarcoma. In this report we present a case of a female with a large swelling with multilobulations over the anterolateral aspect of the left thigh and gluteal region. Incision biopsy revealed a lipoma for which primary excision was done safeguarding vital structures. The lipoma was unusual in its size, its appearance and site of occurrence. Histopathology and immunochemistry revealed it to be a lipoma.